Dose Analysis of Brain Cancer Therapy with Boron Neutron Capture Therapy (BNCT) using PHITS V.3.33 - Sulistiawati, Alfiyah; Pramono, Subur; Pratiwi, Beta Nur; Wijaya, Gede Sutrisna; Triatmoko, Isman Mulyadi; Sardjono, Yohannes; Nuraeni, Nunung; Prasetio, Heru; Hidayati, Nur Rahmah; Ulya, Syarifatul; et al. (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2026)
Based on World Health Organization (WHO) statistics, brain cancer ranks 19th in the world with 321,731 cases, and deaths from brain cancers rank 12th with 248,500 cases, giving an overall mortality rate of 77.24%. One type of brain cancer, glioblastoma (GBM), attacks glial cells and belongs to the glioma category. MRI imaging is used to create geometric images of brain cancers. BNCT is known for its ability to destroy cancer cells in a single treatment or cleavage session. Using PHITS (Particle and Heavy Ion Transport Code System) code in geometric model simulation can help plan radiotherapy. The aim of this study is to analyze the absorbed dose to each organ and determine the shortest irradiation time for the irradiation direction. This study also used 90° (Left-Lateral) and 0° (postero-anterior) angular orientations with boron concentrations of 40 μg/g, 80 μg/g, 100 μg/g, and 150 μg/g. The results showed that this study’s 90° angle orientation (L-LAT) with a boron concentration of 150 µg/g was more optimal. The shortest exposure time is 33.18 minutes, resulting in the following absorbed doses: the skin receives 1.7 Gy, which is below the dose tolerance limit of 2 Gy; the spinal organ absorbs 13.4 Gy, situated below the tolerance limit of 14 Gy; and the brain receives 2.8 Gy, remaining under the tolerance limit of 3 Gy.